A study on the effects of andrographis paniculata (hempedu bumi) on serum protein c, protein s activity and fasting blood glucose in patients with type 2 diabetes mellitus - Basiam, Suhaila (2011)
Background and Objectives Patients with type 2 diabetes mellitus (DM) show enhanced activation of the blood coagulation system and decrease level of natural anticoagulant such as protein C and protein S. This is believed to contribute to the high incidence of premature atherosclerosis attributable to myocardial infarction, cardiovascular disease and peripheral vascular disease in diabetic patients. Andrographis paniculata (Hempedu bumi) has been well known to have blood sugar lowering properties in diabetes patients and has been used by local Malaysians as an alternative to current oral hypoglycaemic agents. With the benefit of its blood sugar lowering properties it is hoped that Andrographis paniculata may also increases level serum protein C and protein S in diabetic patients, thus reducing the risk of atherosclerotic disease. This study was conducted to determine the changes in fasting blood sugar levels and to assess the changes in serum protein C and protein S activity following oral administration of Andrographis paniculata among type 2 diabetes mellitus patients in Hospital Universiti Sains Malaysia (HUSM) Diabetic Medical Clinic. Methodology This is an open-labelled, randomised treatment versus control study which was conducted among type 2 diabetes mellitus patient on follow up at the Hospital Universiti Sains Malaysia (HUSM) Diabetic Medical Clinic from August 2010 till November 2010. A total of thirty four subjects were recruited in this study. Of this, 17 were randomly given the study medication; two tablets each containing 250 mg of Andrographis paniculata for two weeks duration while the other 17 patients were allowed to continue with their previous medication without any alteration. Fasting blood glucose (FBG), serum protein C and protein S, blood samples were taken at baseline and after two weeks intervention for both groups. Results A total number of 34 patients were involved in this study. The mean age was 55.2 ± 9.8 years. The baseline HbA1c was 9.2% ± 2.4 % in both groups. The mean fasting blood sugar during pre intervention in the control group was 8.6 mmol/L ± 3.7 while in treatment group is 9.1 mmol/L ± 5.0 and post treatment, the mean fasting blood sugar was 8.3mmol/L ±2.9 and 9.3 mmol/L ± 4.0 respectively. The mean of protein C in the pre intervention for control group was 117.2 %± 17.3 and in the treatment group was 125.1 % ± 21.3. Post intervention mean protein C in the control group was 121.1 % ± 25.4 and in the treatment group is 125.9 % ± 18.9. The mean protein S in the pre intervention for control group was 202.4 % ± 128.0 and for treatment group is 135.4% ± 30.1 while in the post intervention mean for control group was 208.3 % ± 129.5 and in the treatment group 134.1 % ±25.3. The mean difference of fasting blood sugar, protein C and protein S between pre and post intervention for both groups were statistically not significant. Conclusion Our study demonstrated that generally the blood sugar control among type 2 diabetic patients is still poor with mean HbA1c of 9.2 % ± 2.4. There were no significant changes in mean serum fasting blood glucose, protein C and protein S for pre and post - treatment of oral administration of 500 mg of Andrographis paniculata for two weeks duration in the treatment group when compared to control group. These findings were probably related to inadequate dose of Andrographis paniculata since there was no study of bioequivalence in this study and also inadequate study duration to produce desirable effects in this study.